Assessment of on-time vaccination coverage in population subgroups: A record linkage cohort study. Issue 28 (27th June 2018) - Moore, Hannah C.; Fathima, Parveen; Gidding, Heather F.; de Klerk, Nicholas; Liu, Bette; Sheppeard, Vicky; Effler, Paul V.; Snelling, Thomas L.; McIntyre, Peter; Blyth, Christopher C.; ,
Abstract: Reported infant vaccination coverage at age 12 months in Australia is >90%. On-time coverage of the 2–4–6 month schedule and coverage in specific populations is rarely reported. We conducted a population-based cohort study of 1.9 million Australian births, 1996–2012, combining individual birth and perinatal records with immunisation records through probabilistic linkage. We assessed on-time coverage across 13 demographic and perinatal characteristics of diphtheria-tetanus-pertussis vaccines (DTP) defined as vaccination 14 days prior to the scheduled due date, to 30 days afterwards. On-time DTP vaccination coverage in non-Aboriginal infants was 88.1% for the 2-month dose, 82.0% for 4-month dose, and 76.7% for 6-month dose; 3-dose coverage was 91.3% when assessed at 12 months. On-time DTP coverage for Aboriginal infants was 77.0%, 66.5%, and 61.0% for the 2–4–6 month dose; 3-dose coverage at 12 months was 79.3%. Appreciable differences in on-time coverage were observed across population subgroups. On-time coverage in non-Aboriginal infants born to mothers with ≥3 previous pregnancies was 62.5% for the 6-month dose (47.9% for Aboriginal infants); up to 23.5 percentage points lower than for first-borns. Infants born to mothers who smoked during pregnancy had coverage 8.7–10.3 percentage points lower than infants born to non-smoking mothers for the 4- and 6-month dose. A linear relationship was apparent between increasing socio-economic disadvantage and decreasing on-time coverage. On-time coverage of the 2–4–6 month schedule is only 50–60% across specific population subgroups representing a significant avoidable public health risk. Aboriginal infants, multiparous mothers, and those who are socio-economically disadvantaged are key groups most likely to benefit from targeted programs addressing vaccine timeliness.